Oakeshott on the Character of Religious Experience: Need There Be a Conflict Between Science and Religion? - Fuller, Timothy (Zygon, 2009)
Abstract. Michael Oakeshott reflected on the character of religious experience in various writings throughout his life. In Experience and Its Modes (1933) he analyzed science as a distinctive “mode,” or account of experience as a whole, identifying those assumptions necessary for science to achieve its coherent account of experience in contrast to other modes of experience whose quests for coherence depend on different assumptions. Religious experience, he thought, was integral to the practical mode. The latter experiences the world as interminable tension between what is and what ought to be. The question, Is there a conflict between science and religion? is, in Oakeshott's approach, the question, Is there a conflict between the scientific mode of experience and the practical mode? Insofar as we tend to treat every question as a practical one, these questions seem to make sense. But Oakeshott's analysis leads to the view that scientific experience and religious experience are categorically different accounts of experience abstracted from the whole of experience. They are voices of experience that may speak to each other, but they are not ordered hierarchically. Nor can either absorb the other without insoluble contradictions.